Income Distribution among Women through Local Wisdom in Indigenous Communities (Saemaul Undong Spirit Approach) - Hahury, Hendri Dony; Oppier, Hermi; Pattimahu, Terezia V (Universitas Pattimura, 2025)
This study examines communities' efforts to address income distribution inequality by leveraging local wisdom mechanisms. Income inequality is observed at regional and national levels and manifests in gender disparities. This research aims to explore how local wisdom, particularly the practice of